Gestão de pequenos municípios: primeiros passos na execução de um cadastro territorial multifinalitário rural - Fernandes, Gustavo (2022)
Smaller cities in Brazil face greater difficulties in implementing Rural Multipurpose Territorial Cadasstre (RMTC), due to its elevated cost and lack of specific norms. Thus, it is necessary to develop cost-effective methodologies that can supply RMTC with a more accessible character to all Brazilian cities, regardless of their size. Geotechnologies are useful to this purpose. Using low-cost or free remote sensing products and automatic image classification techniques, it is possible to reduce the implementation costs of RMTCs. There are many images obtained by orbital sensors that are available without cost and which can provide information suitable to rural area mapping. This thesis developed a methodology of RMTC application that is efficient and low-cost, appropriate for application in small cities. The methodology consisted in obtaining a database composed by Planet, Sentinel-2, and Google Satellite images, which have adequate spatial resolution to rural mapping. The targets that are relevant to RMTC were mapped using two different approaches: automatic image segmentation and classification using Google Earth Engine and manual vectorization of targets that could not be classified automatically; RMTC data that is freely available online by other agencies were adjoined to the data obtained in this study and therefore were organized in an easy maintenance and accessibility WebGIS. With the obtained information, it was estimated that 27.95% of the city area is used for pasture, 33.64% is used for agriculture, and the remaining 38.41% is composed by forest areas. It was possible to estimate data over the livestock production capacity in the year of the study and carry out analyzes of the municipality's compliance with environmental conservation laws. In the present work, it was possible to use geoprocessing technologies to create a methodology capable of introducing RMTC in the administration of small municipalities, using free and robust products.